Die Rolle Johann Peter Kirschs bei der Gründung des Päpstlichen Instituts für Christliche Archäologie - Heid, Stefan (Römische Quartalschrift für christliche Altertumskunde und Kirchengeschichte, 2025)
"Johann Peter Kirsch's role in the founding of the Pontifical Institute for Christian Archaeology" - This article describes the efforts made since the end of the First World War to found a papal archaeological institute. Pius XI led this project to success, also thanks to his high esteem for Johann Peter Kirsch, who promoted the foundation from Fribourg in close collaboration with Giulio Belvederi. Kirsch discussed all matters relating to the young institute with the Pope.